2020
DOI: 10.3389/fendo.2020.00203
|View full text |Cite
|
Sign up to set email alerts
|

Early Endothelial Dysfunction in Type 1 Diabetes Is Accompanied by an Impairment of Vascular Smooth Muscle Function: A Meta-Analysis

Abstract: Background: A large yet heterogeneous body of literature exists suggesting that endothelial dysfunction appears early in type 1 diabetes, due to hyperglycemia-induced oxidative stress. The latter may also affect vascular smooth muscles (VSM) function, a layer albeit less frequently considered in that pathology. This meta-analysis aims at evaluating the extent, and the contributing risk factors, of early endothelial dysfunction, and of the possible concomitant VSM dysfunction, in type 1 diabetes. Methods: PubMe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 111 publications
0
26
0
Order By: Relevance
“…Still, the association between cfPWV and FMD in our type 1 DM population raises the possibility that dysglycemia or perhaps insulin resistance, even in the absence of other cardiovascular risk factors, increases the risk of both vascular endothelial and arterial wall dysfunction. Along these lines, a recent meta-analysis of 58 studies examining endothelial function in persons with type 1 DM (n= 2,322) and healthy controls (n= 1,777) corroborated the presence of early endothelial and vascular smooth muscle dysfunction in children and adults with type 1 DM 48 . The study also reported that endothelial dysfunction seems to be more pronounced within macrovascular than microvascular beds, fostering the debate on their relative temporal appearance.…”
Section: Discussionmentioning
confidence: 88%
“…Still, the association between cfPWV and FMD in our type 1 DM population raises the possibility that dysglycemia or perhaps insulin resistance, even in the absence of other cardiovascular risk factors, increases the risk of both vascular endothelial and arterial wall dysfunction. Along these lines, a recent meta-analysis of 58 studies examining endothelial function in persons with type 1 DM (n= 2,322) and healthy controls (n= 1,777) corroborated the presence of early endothelial and vascular smooth muscle dysfunction in children and adults with type 1 DM 48 . The study also reported that endothelial dysfunction seems to be more pronounced within macrovascular than microvascular beds, fostering the debate on their relative temporal appearance.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, dysfunctional osteoblastic niches and microangiopathy damage to the blood vessels in the bone resulting in an impaired ability to egress these cells into circulation in response to ischemia 50 . Microvascular dysfunction and altered blood flow can occur in the early stages of Type 1 diabetes, with hyperglycaemia and oxidative stress reducing the bioavailabilty of nitrix oxide 51 , 52 . Endothelial nitrix oxide synthase induces smooth muscle relaxition and blood vessel dilation, and is strong modulator of circulating angiogenic cells funtion and homing 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, glycated LDL-c has increased susceptibility towards oxidation, which is considered a crucial step in atherogenesis [ 45 ]. Hyperglycemia was associated with preclinical atherosclerotic CVD in studies that included surrogate measures such as carotid intima–media thickness (CIMT) [ 46 ], arterial stiffness [ 47 ], and endothelial function [ 48 ] in T1D.…”
Section: Cardiovascular Risk Factors In Type 1 Diabetes Youths and The Role Of Sexmentioning
confidence: 99%